Estimating Variograms of Soil Salinity Properties by Kriging, Remote Sensing and GIS Techniques in Indira Gandhi Nahar Pariyojana Irrigation Command of Rajasthan, India - Subramoniam, S Rama; Bera, A K; Sharma, J R (Annals of Arid Zone, 2016)
Assessment of soil salinization in irrigated agriculture is important for evaluation of the long term sustainability of agricultural production. Development of salinity in the Indira Gandhi Nahar Pariyojana (IGNP) stage-I irrigation command of Rajasthan is emerging as a serious problem. Reliable estimates of spatial distribution of soil salinity is necessary from the crop management point of view. Soil pH and EC (Electrical Conductivity) were measured in 380 samples collected from various locations in the IGNP stage-I command. The data on pH and EC were interpolated with various semi-variogram models viz., linear, spherical, circular, exponential and Gaussian by ordinary kriging method. Among all the models evaluated, the exponential model showed the best result for the spatial variability in salinity. The semi-variogram maps prepared can be used for the identification of soil sampling locations precisely while mapping at the cadastral level/large scale. The study also demonstrated the possibility of mapping soil salinity using ordinary kriging methods. Key words: Soil salinity, kriging, spatial variability and soil heterogeneity.